Prevalence and associated factors of diabetic nephropathy at Tikur Anbessa Comprehensive Specialized University Hospital, Addis Ababa, Ethiopia - Aberra, Theodros; Feleke, Yeweyenhareg; Tarekegn, Getahun; Bikila, Demere; Melesse, Mehari (African Journal of Nephrology, 2022)
Introduction: Given the global prevalence of diabetes, diabetic nephropathy and its consequences are among the major causes of morbidity and mortality in diabetic populations. However, the prevalence and determinants of diabetic nephropathy in Ethiopia are little studied, and were the main objectives of this study. Methods: A cross-sectional study design was followed among 340 randomly selected diabetic patients attending the national diabetes referral clinics at the diabetes centre of Tikur Anbessa Specialized Hospital, Addis Ababa, using an interviewer-administered structured questionnaire. A total of 340 patients were involved, of whom 200 (59%) were females and 256 (75%) had type 2 diabetes mellitus. Urine and blood samples were drawn from the study population and the corresponding biochemical analyses were conducted at the Ethiopian Public Health Research Institute. Results: The mean age of the participants was 51.6 years (range 18–94 years). The median duration of their diabetes was 11 years (range 1–40 years). Forty-eight pecent of the patients were hypertensive. Only half of the hypertensive cases (53%) were using angiotensin-converting enzyme inhibitors, either alone or in combination with other antihypertensive medicines. Eighty-two percent of the participants had poorly controlled diabetes, with glycated haemoglobin >7%. None was using Sodium-glucose cotransporter 2 (SGLT2) inhibitors or glucagon-like peptide agonists. Some (109, 32%) of the participants were diagnosed with diabetic nephropathy in addition to reduced estimated glomerular filtration rate and albuminuria. Age, dyslipidaemia, educational status, presence of diabetic retinopathy, and elevated triglyceride levels were found to be significant predictors of the condition (P < 0.05). Conclusions: Diabetic nephropathy was present in nearly one-third of the diabetics in the study population. The management of diabetes with renoprotective agents, such as renin–angiotensin–aldosterone system inhibitors and SGLT2 inhibitors, are likely to be very important in this context.